A new high-resolution hydrodynamic model for the coastal Beaufort Sea in the Arctic Ocean: model construction and evaluation - J. Blake Clark; J. Blake Clark; Wesley Moses; Ahmed El-Habashi; Maria Tzortziou; Kyle J. Turner; Hisatomo Waga; Hisatomo Waga; Steven Ackelson; Jonathan Sherman; Jonathan Sherman (Frontiers in Marine Science, 2025)
The aquatic environment of the coastal Arctic is rapidly changing, and understanding how this change will affect the coastal ocean is critical across sectors. To address this, a three-dimensional (3-D) hydrodynamic model was constructed, spanning the coastal Beaufort Sea from −153° to −142° W, explicitly including river delta channels and lagoons, and extending to the continental shelf. The Finite Volume Community Ocean Model (FVCOM) was used to predict ocean physical properties from January 2018 to September 2022, including dynamic sea ice and landfast ice. Model calibration and validation were conducted using a variety of data sources, including in situ hydrodynamic data from oceanographic cruises and moorings. Overall, the model captured interannual temperature variation at Prudhoe Bay from 2018 to 2022 with a model efficiency (MEF) score > 0 (better than the average) for all years (MEF = 0.59, 0.63, 0.23, 0.46, and 0.55). The seasonal temperatures in 2018 and 2019 at bottom-mounted moorings were also well captured (R2 = 0.80–0.90), and sea surface height (SSH) was compared to hourly observations at Prudhoe Bay, with both the low-frequency (R2 = 0.42) and diurnal (R2 = 0.71) variations validated over the model period. Modeled salinity and water current velocity had mixed results compared to the observations: seasonal trends in salinity were generally captured well, but hypersaline lagoon conditions in the winter were not replicated. Measured bottom water velocity proved difficult to recreate within the model for any given point in time from 2018 to 2019. Covariance analyses of the surface wind velocity, SSH, and current velocity indicated that wind forcing significantly correlated to errors in local SSH predictions. Current velocity covaried substantially less with SSH and wind velocity, with large differences across the three moorings: this suggests that local factors such as bathymetry and shielding by islands are likely important. Future work building on this system will include analyses of the drivers of landfast ice and sea ice breakup; the potential for erosion via waves, large storms, and elevated surface temperatures; and the linkage to an ecosystem model that represents processes from carbon cycling to higher trophic levels.